‘I got into the room by means of a picklock key and found him’ Complex Prepositions in Early Modern English - Romero-Barranco, Jesús; Calle-Martín, Javier (My University, 2016)
English complex prepositions can be subdivided into two-word and three-word sequences, the former containing an adverb, adjective or conjunction together with a simple preposition (i.e. instead ADV of PREP ); and the latter being composed of a preposition + noun + preposition (i.e. by PREP means NOUN of PREP ) (Quirk et al. 1985: 669-670). The complex prepositions BY WAY OF and BY MEANS OF are the result of a process of grammaticalization in which they lost part of their lexical functions and later were reanalysed as functional elements expressing instrumentality (Hoffman 2005: 71-76). From an etymological point of view, these words have different backgrounds. The word WAY, on the one hand, can be traced back to the Old English period (c. 950), with the meaning of ‘road, path’ (OED). MEAN, on the other, is a French borrowing, first attested in 1374, with the meaning of ‘an intermediary agent or instrument’ (OED). As complex prepositions in English, BY WAY OF and BY MEANS OF were first attested in 1390 and 1427, respectively (OED). The present paper has been conceived with the following objectives: 1) to assess the grammaticalization process by which nouns such as WAY and MEAN developed prepositional functions meaning instrumentality; 2) to analyse the use and distribution of BY WAY OF and BY MEANS OF in the History of English; and 3) to determine any likely preference in terms of the informants’ gender and social class. The source of evidence comes from the the Corpus of Early English Correspondence and the Old Bailey Corpus.
Keywords: Inglés - Preposición; Competition; Grammaticalization; By means of; By way of; Diachrony